Notes on the result of solutions of the equilibrium equations - Gaiping He; Lihong Wang; Ben Rodrigo (Boundary Value Problems, 2018)
Abstract In this short note, we correct some expressions obtained by Wang et al. (Bound. Value Probl. 2015:230, 2015). The corrected expressions will be useful for evaluating the boundary behaviors of solutions of modified equilibrium equations with finite mass subject. Moreover, the correction of Theorem 2.1 is also given.